Fading Suppression for Distributed Acoustic Sensing Assisted With Dual-Laser System and Differential-Vector-Sum Algorithm - Li, Hao; Liu, Tao; Fan, Cunzheng; Yan, Baoqiang; Chen, Junfeng; Huang, Tianye; Yan, Zhijun; Sun, Qizhen (IEEE sensors journal, 2022)
The sensing performance is severely affected by the intensity fading in the phase-sensitive optical time domain reflectometry ( φ -OTDR) based distributed acoustic sensing (DAS) system. The intensity fading manifests a stochastic amplitude fluctuation in the scattering signal. To suppress the fading noise, a heterodyne φ -OTDR system assisted with dual lasers with independent frequency, polarization, and initial phase is established to generate two pulses responses with different fading components at the same time. The backscattering signals from two individual probe pulses present different fading positions but possess the same phase change rate which is induced by the external disturbance. Through the differential-vector-sum algorithm including vectorization and phase differential, two complex Rayleigh backscattering beat signals from the two laser probes are efficiently synthesized, to simultaneously suppress the fading phenomenon caused by the inner pulse interference, polarization mismatch and phase mismatch. In the experimental validation, the probability of the fading channels in dual-laser scheme was significantly reduced from 9.4% to 1% compared with the single laser system, which is based on the resolution threshold of 2.1n ε / \surd Hz at 10Hz. Moreover, the dual-laser scheme also proves the polarization insensitivity by inducing a rapid polarization perturbation for two probe lasers. Owing to the fading noise suppression, the dynamic signal's SNR of the dual-laser system was improved more than 20dB in the intensity fading channels, while the temporal and spatial resolution were not deteriorated. The proposed fading suppressed distributed sensing system possesses the excellent performance, which makes it play an important role for practical distributed acoustic sensing.